Anions mediated amino-type Cd-MOFs catalysts for efficient photocatalytic hydrogen evolution - Qian, Jun-Feng; Yue, Hua-Dong; Qiu, Peng-Xiang; Liang, Qian; Hang, Meng-Ting; He, Ming-Yang; Bu, Yun-Fei; Chen, Qun; Zhang, Zhi-Hui (Journal of solid state chemistry, 2021)
Photocatalytic water splitting can be used to directly transfer solar energy into chemical energy with highly efficiency. Metal-organic frameworks (MOFs) materials are well known on the advantages of high design flexibility and metal center functionalization. In this study, a series of Cd-centered MOFs were successfully fabricated by a simple solvent evaporation method based on the different anion mediated pyridyl leucine derivatives. Single-crystal X-Ray diffraction showed the isostructural 3D chiral coordination networks of three Cd-MOFs with helical chains connected by the adjacent carboxylate groups. Within the helical coordination chains, the formate (For) and acetate (OAc) anions adopted chelate modes in Cd-LFor and Cd-LOAc, whereas the chloride worked as a monodetate ligand in Cd-LCl. Powder X-ray diffraction (PXRD), Thermogravimetric analysis, UV–vis spectra, Photocurrent-time test (I-t) and Mott-Schottky (MS) curves were carried out to characterize and analysis these Cd-MOFs. All the samples exhibit photocatalytic activity for hydrogen generation in aqueous solution of Na2S/Na2SO3 upon irradiation at full light. The photocurrent time test showed that Cd-LCl showed a higher photocurrent intensity than those of Cd-LFor and Cd-LOAc, which proved the lower electron-hole recombination and correspondingly higher hydrogen production photocatalysis active. The highest H2 production rate reached 17242 ​μmol ​g−1 ​h−1 for Cd-LCl. In the photocatalytic reaction, the hydrogen production rate was stable without significant decrease, indicating that the material had no significant deactivation and had good photocatalytic activity. Novel anion mediated amino-type Cd-MOFs exhibit photocatalytic activity for hydrogen generation in aqueous solution with Na2S/Na2SO3 as the sacrificial agents upon irradiation at full light, in which amino and chloride promote the photocatalysis performance. [Display omitted] •Novel anion mediated amino-type Cd-MOFs were synthesized and adopted unique 3D coordination network with solvent channels.•All the Cd-MOFs exhibit photocatalytic activity for hydrogen generation in aqueous solution upon irradiation at full light.•The amino group and the doping chloride led to good photocatalytic water splitting performance of Cd-LCl.